2016
DOI: 10.1176/appi.ps.201400544
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Psychiatric Practice Guidelines on Medication Costs and Youth Aggression in a Juvenile Justice Residential Treatment Program

Abstract: Implementing psychiatric practice guidelines in juvenile justice facilities can reduce psychotropic medication costs without an increase in youth aggression. Implementation of the guidelines requires an organized psychosocial treatment program to help deter an inappropriate focus on psychotropic treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 54 publications
(51 reference statements)
1
21
0
1
Order By: Relevance
“…Three studies focused on management staff and/or teams, with sample sizes ranging from 32 (teams) to 75 (staff) [21,31,35]. Eight studies measured EBP impact on the organization/ agency or system and had sample sizes ranging from 3-307 organizations [22,24,26,27,30,32,33,36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies focused on management staff and/or teams, with sample sizes ranging from 32 (teams) to 75 (staff) [21,31,35]. Eight studies measured EBP impact on the organization/ agency or system and had sample sizes ranging from 3-307 organizations [22,24,26,27,30,32,33,36].…”
Section: Resultsmentioning
confidence: 99%
“…The remainder were published in specialty journals related to public health (four articles [20][21][22][23]), children's services (one article [19]), or implementation science (one article [24]). Several studies focused on specific demographic groups [children with substance use disorders, mental health disorders, or trauma (six articles [19,[23][24][25][26][27]), adolescents/youth with mental health disorders (two articles [21,28]), justice-involved youth (two articles [29,30]), geriatric mental health (one article [20]), and veteran's mental health (one article [31]). Studies focusing on specific diagnoses included: alcohol use (one article [32]), addiction (one article [33]), co-occurring disorders (one article [34]), mental health disorders (two articles [22,35]), and serious mental illness (one article [36]).…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…It seems to be especially common among children/youth who have experienced several changes of care environments (Bertram, Narendorf, & McMillen, ; McMillen, Fedoravicious, Rowe, Zima, & Ware, ; Narendorf et al, ). Results from several studies question the often alleged benefits of psychotropic medications on placement stability and rates of disruptive behaviour of children/youth in out‐of‐home care (Bellonci et al, ; Lee, Walker, & Bishop, ; Tai, Shaw, & dos Rheis, ). Two recent studies examined the effects of systematic re‐assessments on prescribed psycho‐pharmaceuticals for youth in residential care.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies examined the effects of systematic re‐assessments on prescribed psycho‐pharmaceuticals for youth in residential care. Both found that relatively radical reductions of such medications did not result in an increase of youths’ aggressive behaviour (Bellonci et al, ; Lee et al, ). In fact, Bellonci et al () reported substantial decreases in the number of assaultive incidences and in the use of physical restraints.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies within paediatric populations have demonstrated that psychotropic polypharmacy and antipsychotics can be safely reduced within residential treatment centres without re-emergence of challenging behaviours in children 28–33. Moreover, researchers observe reductions in adverse events and side effects,29 32 as well as substantial cost savings 10 34…”
Section: Introductionmentioning
confidence: 99%